2016
DOI: 10.1007/s40279-016-0488-y
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Physical Activity in the Heart of the NHS: The Need for a Whole-System Approach

Abstract: Solutions to the global challenge of physical inactivity have tended to focus on interventions at an individual level, when evidence shows that wider factors, including the social and physical environment, play a major part in influencing health-related behaviour. A multidisciplinary perspective is needed to rewrite the research agenda on physical activity if population-level public health benefits are to be demonstrated. This article explores the questions that this raises regarding the particular role that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 42 publications
1
49
0
1
Order By: Relevance
“…However, despite these aspirations, it has been suggested that there is little evidence that PA is being comprehensively promoted in healthcare settings 15. The barriers to increasing health promotion and preventative care in healthcare settings are consistent across professional groups and include lack of time, perceived lack of knowledge, lack of confidence and lack of organisational support 16–18…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these aspirations, it has been suggested that there is little evidence that PA is being comprehensively promoted in healthcare settings 15. The barriers to increasing health promotion and preventative care in healthcare settings are consistent across professional groups and include lack of time, perceived lack of knowledge, lack of confidence and lack of organisational support 16–18…”
Section: Introductionmentioning
confidence: 99%
“…HCP are considered desired, credible and well-placed messengers for the delivery of PA advice (11,17).…”
Section: Strategies To Optimize Pa Prescription Among Hcpmentioning
confidence: 99%
“…Among CF patients, regular physical activity (PA) has the potential to decrease the annual rate of decline in pulmonary function, improve airway clearance, reduce hospitalization frequency and improve longevity, while also improving aerobic capacity, muscle strength, bone health and enhancing health-related quality of life (9,10). The HCP plays an integral role in the promotion of PA behaviours among their patients (11). According to the American College of Sports Medicine Exercise is Medicine initiative, all HCP should incorporate discussions about PA and exercise into every patient interaction (12).…”
Section: Introductionmentioning
confidence: 99%
“…There was also an over-representation of physiotherapists within the current study as a result of the survey invitation being sent to the National Physiotherapy CF Clinical Interest Group and not to other professional clinical interest groups. Also, as the nature the data is self-reported, there is a risk that social desirability bias may have occurred making the results more desirable and portraying a less realistic representation of current knowledge and practice 12,20 . Clinical exercise physiologists and exercise scientists were not included in this survey as the has not yet been recognized by the Health Service Executive in Ireland.…”
Section: Limitationsmentioning
confidence: 99%